Education for Citizenship: Student motivation and satisfaction - Casillas Martín, Sonia (2019)
Education for Citizenship is a requirement if we consider learning as a lifelong process that allows us to face the reality of each moment and context, based on a standard policy of recognition of Citizenship and education as a key strategy. The article aims to present the results of research that analyses the motivation and self-perceived satisfaction of 700 Spanish Compulsory Education students about the subject Education for Citizenship. Data were collected through an ad-hoc questionnaire and analysed with multivariate and inferential skills, parametric and homoscedasticity tests, as well as the Receiver Operating Characteristic Curve. The main conclusion points out that motivation has a remarkable impact on students’ satisfaction. Gender, age, or centre have thereon no impact.